Electoral Rentierism? The Cross-National and Subnational Effect of Oil on Electoral Competitiveness in Multiparty Autocracies - Michael Wahman; Matthias Basedau (German Institute of Global and Area Studies (GIGA), 2015)
Building on theoretical insights from research on the rentier state and the "resource curse," several studies have supported the argument that oil hinders democracy. However, previous research on the rentier state has neglected the global surge of multiparty autocracies or "electoral authoritarian" regimes since the end of the Cold War. No systematic study has been carried out on the question of whether or not and how oil affects electoral contests in nondemocratic regimes. In this paper we contribute to filling this gap by combing the literature on multiparty autocracy and the political economy of the rentier state. As oil production creates substantial, nontransparent revenue streams to national and subnational governments, we hypothesize that oil production has a negative effect on electoral competitiveness, both cross- and subnationally, in multiparty autocracies. Consequently, the democratic "resource curse" emphasized in earlier work on the rentier state is likely to persist even after the introduction of multipartyism in cases where oil production predates democratic institutions. The paper tests the hypothesis cross-nationally, using data on all multiparty elections held in the world in the period 1975 - 2010, and subnationally, using a new data set on subnational election results and oil production in Nigeria. Our results confirm that oil impedes electoral competitiveness, both cross- and subnationally, in multiparty autocracies.
Keywords: 300; oil; authoritarianism; elections; Nigeria; competition; Africa